Challenges of Marketing Information Resources and Services in University Libraries in Bayelsa State Nigeria - Ogunbodede, Kolawole Francis; OKwu, Emmanuel (Department Library of Governance Institut of Home Affairs, 2023)
Background: University libraries in Nigeria are confronting the issue of underutilization of their resources and services, which can be ascribed to weak marketing efforts. Purpose: This study aimed at examining the challenges of marketing information resources and services in university libraries in Bayelsa State Nigeria. Method: A descriptive survey design was used for the investigation. The study population included 52 librarians from four university libraries in Bayelsa State. A total enumeration sample strategy was used to collect data via an online questionnaire. The questionnaire was distributed to 52 librarians, and 47 responded, yielding a 90% response rate. The data were analysed using frequency counts and simple percentages. Results: The results of the study show that all university libraries in Bayelsa State use a variety of marketing techniques to advertise their information resources and services, including library orientation, user education, social media platforms, exhibitions, and displays. Effective marketing efforts in these libraries were, however, hampered by issues like insufficient budget, poor Internet connectivity, a lack of marketing policies, and the absence of a specialized marketing staff. Conclusion: Based on the findings, the researchers concluded that university libraries should be supported by adequate funding, improve Internet connectivity, establish a dedicated marketing department or team, collaborate with academic departments and faculty, gather user feedback, and invest in professional development opportunities to enhance marketing efforts. Keywords: Challenges of Marketing; Information Resources and Services; University Libraries; Bayelsa State